Left atrial late gadolinium enhancement with water–fat separation: The importance of phase‐encoding order. Issue 1 (16th September 2013) - Shaw, Jaime L.; Knowles, Benjamin R.; Goldfarb, James W.; Manning, Warren J.; Peters, Dana C.
Abstract : Purpose: To compare two late gadolinium enhancement (LGE) cardiovascular magnetic resonance (CMR) methods: a Dixon LGE sequence with sequential phase‐encoding order, reconstructed using water–fat separation, and standard fat‐saturated LGE. Materials and Methods: We implemented a dual‐echo Dixon LGE method for reconstructing water‐only images and compared it to fat‐saturated LGE in 12 patients prior to their first pulmonary vein isolation (PVI) procedure. Images were analyzed for quality and fat‐suppression. Regions of the left atrium were evaluated by a blinded observer (1 = prominent enhancement, 0 = mild or absent enhancement) on two sets of images (fat‐saturated and water‐only LGE) and agreement was assessed. Results: Water‐only LGE showed a trend toward better fat‐suppression ( P  = 0.06), with a significantly more homogeneous blood pool signal and reduced inflow artifacts (both P  < 0.01). Agreement between fat‐saturated LGE and water‐only methods was found in 84% of regions, significantly correlated by chi‐squared test ( P  < 0.001). The kappa value was 0.52 (moderate). The average number of enhancing segments was higher for fat‐saturated LGE than water‐only LGE (4.2 ± 2.7 vs. 3.2 ± 2.9, P  = 0.03). Conclusion: The two‐point Dixon LGE technique reduces artifacts due to a centric k ‐space order. A similar enhancement pattern was observed irrespective of the LGE technique, with more enhancement detected by fat‐saturated LGE.J. Magn. Reson. Imaging 2014;40:119–125 . ©2013 Wiley Periodicals, Inc .